Improved crop productivity and soil properties under varying planting densities of Pentaclethra macrophylla Benth. and Acacia auriculiformis A. Cunn. in Congo Basin - Mapenzi, N.; Katayi, A.L.; Bauters, M.; Masimane, J.; Schure, J.; Kweyu, R.; Nabahungu, N.L. (Springer, 2024)
Soil fertility depletion is a major constraint to agricultural production in the Congo Basin and is aggravated by climate change. Therefore, agroforestry systems (AFS) are used to improve soil fertility and crop productivity. Indeed, Pentaclethra macrophylla and Acacia auriculiformis are among the most agroforestry species used in this basin. However, smallholders are limited in their choice of agroforestry species and the spacing. Hence, this study comparatively evaluated the effects of P. macrophylla (native) and A. auriculiformis (exotic) legume tree species on soil macronutrients and food crops’ yield during four cropping seasons. To do this, a multifactor trial design was implemented in Lobilo catchment, Congo Basin, with two tree species, four tree planting densities (T1: 2500 trees × ha−1, T2: 625 trees × ha−1, T3: 278 trees × ha−1; and T0: crop monoculture), and three intercrops (cassava, maize, and peanut). The results revealed that both agroforestry species did not significantly differ regarding their impact on soil macronutrients. The total nitrogen and the pH in soil have increased with the cropping seasons. With regard to the food crops, cassava and maize yield were greater under P. macrophylla than under A. auriculiformis. However, the 2500 trees × ha−1 density negatively affected food crops’ yield and did not allow food crop production after the second cropping season. To maximize the positive effects of these AFS, it is essential to plant or co-plant these two agroforestry species at 625 trees × ha−1 density. Future research could investigate other native species and include water and light interactions.